2014
DOI: 10.1016/j.jvoice.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Voice Use in Teaching Environments: A Field Study Using Ambulatory Phonation Monitor

Abstract: Objectives. This case-control designed field-study examines the vocal behavior in teachers with self-estimated voice problems and their age-, and school-matched voice-healthy colleagues. It was hypothesized that teachers with and teachers without voice problems use their voices differently regarding fundamental frequency, sound pressure level and in relation to the background noise. Methods.Teachers with self-estimated voice-problems (n=14, 2M/12F) were age and gender matched to voice-healthy school-colleagues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 44 publications
(42 reference statements)
4
24
0
Order By: Relevance
“…Cantarella et al [8] found similar values in call centre operators, but these results are difficult to compare since the mean duration of data sampling in the study by Cantarella et al [8] was significantly longer (>7 h). Finally, the average F 0 in SLPs is similar to that reported in female call centre operators (F 0 average 217.8 Hz [8]), while it is lower than that reported in teachers (F 0 average ranging from 237 to 245 Hz [15]), in a previous study on SLPs (F 0 average 247.92 Hz [17]) and in female music students (F 0 average 287.078 Hz [5]), even if the high F 0 in the latter might simply be related to the specific needs essentially pertinent to singing performance. It is possible that these diverging results are related to differences in the studied populations and to the amount of phonation-monitoring performed.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Cantarella et al [8] found similar values in call centre operators, but these results are difficult to compare since the mean duration of data sampling in the study by Cantarella et al [8] was significantly longer (>7 h). Finally, the average F 0 in SLPs is similar to that reported in female call centre operators (F 0 average 217.8 Hz [8]), while it is lower than that reported in teachers (F 0 average ranging from 237 to 245 Hz [15]), in a previous study on SLPs (F 0 average 247.92 Hz [17]) and in female music students (F 0 average 287.078 Hz [5]), even if the high F 0 in the latter might simply be related to the specific needs essentially pertinent to singing performance. It is possible that these diverging results are related to differences in the studied populations and to the amount of phonation-monitoring performed.…”
Section: Discussionsupporting
confidence: 73%
“…Bottalico and Astolfi [7], who studied a group of 40 primary school teachers, reported a percentage of phonation time of 25.9 and 25.1% in female and male teachers, respectively. Lyberg Ahlander et al [15] reported a percentage of phonation time during teaching of 23.6% in a group of 52 teachers, while Hunter et al [17], who analysed a group of 57 teachers, found an average vocalization of 29.9% of the time during working hours. On the other hand, the amplitude average during working activities in SLPs appears to be lower than that of football coaches (amplitude average 83.67 dB SPL [3]) and music students majoring in voice (amplitude average 84.339 dB SPL [5]), while it appears to be similar to that found in call centre operators (amplitude average 70.5 dB SPL [8]), in a previous study on SLPs (amplitude average 75.46 dB SPL) and in teachers (amplitude average ranging from 71 to 75 dB SPL [15]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol is released during stress and previous studies suggest that stress is a risk factor in developing vocal symptoms or dysphonia (Baker, 2008;Dietrich, Verdolini Abbott, GartnerSchmitdt & Rosen, 2008;Dietrich & Verdolini Abbott, 2012;Chen, Chiang, Chung, Hsiao & Hsiao, 2010;Gassull, Casanova, Botey, Amador, 2010;Lyberg Åhlander, 2011;Lyberg Åhlander, Pelegrín García, Whitling, Rydell & Löfqvist, 2014;Rantala, Hakala, Holmqvist & Sala, 2012). About 23-25% of individuals seeking care for voice disorders or with common vocal pathologies show stress scores deviating upwards from normal scores Misono et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…22 Comparing VLI measures with self-assessment measures may therefore help us understand the relationship between phonatory behaviour and the development of voice disorders.…”
Section: Introductionmentioning
confidence: 99%